2020
DOI: 10.3389/fnins.2020.561185
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model of Aminoglycoside-Induced Hyperacusis and Tinnitus

Abstract: Aminoglycosides (AG) such as amikacin are commonly used in cystic fibrosis patients with opportunistic pulmonary infections including multi-drug resistant mycobacterium tuberculous and non-tuberculous mycobacterium. Unfortunately, this class of drugs is known to cause peripheral damage to the cochlea leading to hearing loss that can fluctuate and become permanent over time or multiple exposures. However, whether amikacin can lead to central auditory dysfunction like hyperacusis (increased sensitivity to sound)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 94 publications
9
21
0
Order By: Relevance
“…Additionally, these abnormal behaviors occur in the presence of only a mild loss of hearing sensitivity. These new findings are consistent with prior findings that amikacin can cause these behavioral symptoms following a mild threshold shift, although the mechanism will need to be elucidated (Longenecker et al, 2020; Figure 7). The largest difference between the two studies was that tobramycin treated mice demonstrated less startle magnitude increases after treatment than amikacin treated mice (Figure 5 vs.…”
Section: Hyperacusis and Tinnitus Appear After Tobramycin Treatmentsupporting
confidence: 90%
See 4 more Smart Citations
“…Additionally, these abnormal behaviors occur in the presence of only a mild loss of hearing sensitivity. These new findings are consistent with prior findings that amikacin can cause these behavioral symptoms following a mild threshold shift, although the mechanism will need to be elucidated (Longenecker et al, 2020; Figure 7). The largest difference between the two studies was that tobramycin treated mice demonstrated less startle magnitude increases after treatment than amikacin treated mice (Figure 5 vs.…”
Section: Hyperacusis and Tinnitus Appear After Tobramycin Treatmentsupporting
confidence: 90%
“…A similar finding was observed with the clinically modified or adopted responder criteria (American Speech-Language-Hearing Association, 1994). This finding was comparable to the effect of ebselen on amikacin treated mice (Longenecker et al, 2020), and provides evidence that ebselen or other otoprotective drugs might work at ameliorating AG-induced hearing loss in clinic (Avci et al, 2016;Fox et al, 2016;Dogan et al, 2017;El-Anwar et al, 2018;Apaydin et al, 2021). However, the threshold shifts seen here were drastically different than those found with a similar tobramycin dosing experiment in Swiss-Webster mice (Gu et al, 2020).…”
Section: Tobramycin-induced Temporary Threshold Shifts Can Occur Without Permanent Cochlear Damagesupporting
confidence: 76%
See 3 more Smart Citations